The Maladministration Alleviating Strategy in The Attempt of Facing Society 5.0 In Surakarta - Alya Raissa Abiel; Kristina Setyowati (Indonesian Association for Public Administration (IAPA), 2021)
Maladministration still occurs frequently in some Indonesian areas, including Surakarta city. Various maladministration practices should be alleviated in Surakarta City, for the public service process to be performed maximally and thereby not taking the people’s basic rights to receive the quality public service. Moreover, technology accessibility is getting higher and Indonesia is prepared for entering into society 5.0 Era expectedly more oriented to human beings (human centered). Therefore, this research aims to discuss the strategy of alleviating maladministration in Surakarta City in the attempt of dealing with Society 5.0 era. Then, this research employed a qualitative research method. The analysis technique used in this study was content analysis obtained through literature review. Considering the result of literature review, it can be seen various strategies applicable to alleviate maladministration in the attempt of dealing with Society 5.0 era: improving the quality of Human Resource; Expanding science research and development field; improving communication and technology infrastructure; discussion between practitioners; applying agile government concept; and the last, commitment, consistency, and collaboration between sectors in the attempt of dealing with Society 5.0.